Work Stress as a Mediator between Work-Family Conflict and Work Burnout among Female Employees in the Garment Industry - Zulfa Rahmalia; Maharani Tyas Budi Hapsari (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2026)
This study was conducted to examine the importance of work stress in explaining the relationship between work-family conflict and work burnout among female employees in the garment industry. High work demands and family roles make female employees prone to work fatigue, so work-family conflict is expected to increase work burnout through work stress. This study used a quantitative approach with 114 female employees who were housewives working in the production department of the garment industry as subjects. Data were collected using the work-family conflict scale, job stress scale, and Maslach Burnout Inventory (MBI) scale, which had been adapted to the research context. Data analysis was performed using the Hayes PROCESS Macro Model 4 with the help of IBM SPSS version 22. The results showed that work–family conflict had a significant effect on work stress and work burnout, and work stress acted as a partial mediator in this relationship. These findings emphasize the importance of organizational and social support in helping female employees balance their work and family roles.